(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: Saline sonosalpingography is a simple technique that has previously proved to be one way of increasing the chance of achieving pregnancy for couples with unexplained infertility. Objective: The purpose of the present was to evaluate the pregnancy rate following saline sonohysterography in stimulated cycles for couples with unexplained infertility. Methodology: This study was designed as prospective randomized controlled trial which was carried out for a period of two years from January 2015 to December 2016. Women with unexplained infertility were selected randomly for saline sonosalpingography and the procedure was carried out three to four days before ovulation in stimulated cycle. Outcomes measure were rate of pregnancy, first trimester abortion, multiple pregnancy, ectopic etc. Result: In this study total number of 55 patients were recruited for this study and saline sonosalpingography was performed over 2(two) years. Age range was from 23 to 42 years. Maximum patients are within the age range of 23 to 27 years. Among 55 patients, 23 were pregnant. Pregnancy rate was 41.81% cases. Singleton pregnancy without any complication was 52.17% cases. Twin pregnancy rate was 13.01% cases. Among them twin with single fetus demise was 4.3% cases, missed abortion 21.7% cases and ectopic was 8.7% cases. Conclusion: With good case selection, therapeutic hydrotubation may be beneficial in resource poor countries, especially in patients with incomplete tubal occlusion bilateral perifimbrial adhesions and as part of treatment for unexplained infertility. This demonstrates increased chance of pregnancy in this group. So further evaluation is needed to upgrade the result of the study. Journal of Current and Advance Medical Research 2017;4(2):48-52